2013
DOI: 10.1194/jlr.m030924
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acid reduces adiposity and increases markers of browning and inflammation in white adipose tissue of mice

Abstract: mixtures of cis -9, trans -11 (9,11) conjugated linoleic acid (CLA) and trans -10, cis -12 (10,12) CLA. Indeed, consuming a mixture of these CLA isomers, or 10,12 CLA alone, reduced body fat in many animal (reviewed in Ref. 3 ) and human studies ( 4 ). Rodents that consumed higher amounts of the CLA than humans (e.g., 0.5-1.5% CLA in the diet or 600-1,800 mg/kg body weight) lost body fat more rapidly but concurrently developed side effects, including chronic infl ammation, insulin resistance, and lipoatrophy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
81
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 57 publications
11
81
1
Order By: Relevance
“…In this experimental condition, the pathological signs were improved by both individual CLA isomer supplements; however, 9,11-CLA administration more effectively downregulates pathological changes in the liver (macro-and microvesicular hepatic steatosis and oxidative stress) and in the serum (ALT, GGT, proinfl ammatory cytokines, and chemokines) compared with 10,12-CLA treatment. These results are consistent with the reported different health benefi ts elicited by individual CLA isomers ( 14 ), but the favorable effects exhibited by 10,12-CLA are not in complete agreement with a recent review showing its steatogenic activity ( 33,38 ). The explanation for this discrepancy can be attributed to dosage as well as the different treatments or animal models used.…”
Section: Discussionsupporting
confidence: 78%
“…In this experimental condition, the pathological signs were improved by both individual CLA isomer supplements; however, 9,11-CLA administration more effectively downregulates pathological changes in the liver (macro-and microvesicular hepatic steatosis and oxidative stress) and in the serum (ALT, GGT, proinfl ammatory cytokines, and chemokines) compared with 10,12-CLA treatment. These results are consistent with the reported different health benefi ts elicited by individual CLA isomers ( 14 ), but the favorable effects exhibited by 10,12-CLA are not in complete agreement with a recent review showing its steatogenic activity ( 33,38 ). The explanation for this discrepancy can be attributed to dosage as well as the different treatments or animal models used.…”
Section: Discussionsupporting
confidence: 78%
“…A notable exception is arginase 1 gene expression, which is not significantly affected. We can speculate that the lower degree of stimulation of M2 markers in Shen's study (28), compared with our current data, relies on the distinct sensitivity between male and female mice and between different mouse strains. The mode of t10,c12-CLA administration could also be a factor.…”
Section: Discussioncontrasting
confidence: 46%
“…In a recent study (28), 129Sv male mice were provided with semipurified diets enriched with increasing amounts of t10,c12-CLA (0.03, 0.1, and 0.3% w/w) for 7 wk. Mice receiving the highest dose of the compound displayed increased MCP1, F4/80, TNFa, and IL-6 gene expression in WAT, in line with our current and earlier observations (18).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies in humans have documented elevated levels of C-reactive protein with t10,c12 CLA and elevated isoprostanes with supplementation with either isomer [37,38]. Others have reported that t10,c12 CLA promotes adipose tissue inflammation in mouse adipose tissue, 3T3-L1 preadipocytes and primary human adipocytes [39][40][41][42]. The effect of dietary CLA isomers on the kidney within the context of the obese state remains to be determined.…”
Section: Introductionmentioning
confidence: 91%